AKAD GADAI TANAH PADA MASYARAKAT DESA CANDI KAB. SUMENEP DITINJAU DARI PRESPEKTIF HUKUM ISLAM - Akhyar (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2020)
Abstract In everyday life there are several forms of land pawning / rice fields that are often carried out by our society. As was done by the people of Candi Village, Dungkek. Regency of Sumenep when wanted to pawn their land / rice fields because of economic problems. However, for whatever the reason, very application of muamalah activities held should not contrary with Islamic law. The purpose of this study is to find out how the pawn system is usually done by people of Candi, Dungkek, Regency of Sumenep is viewed by the perspective of Islamic law. This research uses descriptive qualitative method of analysis. The results of this study are the practice of the pawn that occured in Candi Village can be described as that A as a person who wants to provide land came to the B with the intention to borrow money. In the transaction, A gives land (paddy / garden) as collateral for the debt. However, the agreement did not determined who would manage the land. Although in reality the person who managed the land is B, besides B is entitled to take all the benefits resulted from the collateral land, there is also no provision between the two parties about the time period of the pawn, so the pawn recipient will return the pawn land until the owner paying the debt off. Viewed from the perspective of Islamic law, the land pawn contract carried out by the people of Candi Village, Dungkek Sub district, regency of Sumenep, in the terms of the availability of pillars and pawning conditions, is valid in accordance with the provisions of Islamic law, although it still needs improvement, especially clarity in the management and safe keeping of collateral items (marhun). because there is indication of over-exploitation by Murtahin and there is not the clarity of the time of the Pawn, and this resulted in losses to the Rahin.